With Project HOPE – the People-To-People Health Foundation, Inc. “Tuberculosis trends in Uzbekistan” - Kuchimov, Abdunabi (My University, 2014)
Introduction. Despite the availability of effective anti-tuberculosis treatment and public health interventions, tuberculosis (TB) remains a major global health problem. The emergence of resistance to anti-tuberculosis drugs, particularly of multidrug-resistant TB (MDR-TB), continues to threaten the progress made in controlling the disease. Methods. This report summarizes the field experience completed with Project HOPE – People-to-People Health Foundation, Inc. in Uzbekistan from June 17 to August 23, 2013. The primary focus of the field experience was to analyse tuberculosis trends and factors associated with the increasing incidence of multidrug-resistant tuberculosis in Uzbekistan. The analysis is based primarily on data reported by World Health Organization’s (WHO) Member States in annual rounds of global TB data collection. Results. The descriptive analysis of the WHO TB surveillance data shows number of positive changes in trends of TB in Uzbekistan. From 2000 to 2012, both TB incidence and prevalence had gradually decreased. Similar picture was observed in TB mortality rate. Despite some decrease in the notification rate of new and relapse cases, notification rate of previously treated TB cases has noticeable increased during the reporting period. Pulmonary TB remains the main form of TB in Uzbekistan. The age group 25-34 constituted the highest prevalence between 2006 and 2012. The drug susceptibility test (DST) is becoming more accessible in the country and it shows increase in prevalence of multidrug-resistant tuberculosis (MDR-TB). During the study period, there was no much progress in the treatment success rate, because of increasing prevalence of MDR-TB. Conclusion. All aforementioned, even with taking into consideration the limitations of the data, we conclude that the National TB Program is on the right track to reach and close to Millennium Development Goals for 2015.
Keywords: Tuberculosis; MDR-TB; TB burden; HIV; Uzbekistan; Project Hope; Public Health (0573)